Diagnosis of physical and cognitive ergonomic risks in the Department of Logistics at University of Matanzas, Cuba - Pancorbo Camacho, Isabela (2025)
The objective of this research was to diagnose ergonomic risks from both physical and cognitive dimensions in workers at the Logistics Center of the University of Matanzas, Cuba. A quantitative, descriptive, non-experimental, and cross-sectional methodology was applied, involving workers in the roles of warehouse assistant, supply and material technician (TATM), and commercial management technician (TEC). For the physical dimension, the Step Test and the tabular method were used to calculate physical work capacity (PWC) and energy expenditure (EE). For the cognitive dimension, psychophysiological indicators and the Knowledge Work Intensity index were employed. Results showed that warehouse assistants had an EE exceeding their PWC, indicating physical overload. Additionally, moderate mental workload was identified in TATM and TEC positions, with two or more affected indicators. It is concluded that specific ergonomic interventions are needed, including reorganization of work schedules and the implementation of ergonomic training programs. Furthermore, it is recommended to develop institutional policies that prioritize workers’ physical and cognitive well-being as part of a comprehensive prevention strategy.